2021
DOI: 10.1177/10105395211016333
|View full text |Cite
|
Sign up to set email alerts
|

Small Amounts of Physical Activity During the COVID-19 Pandemic May Contribute to Improve Empathy in Young Adults: An Observational Study

Abstract: Decreases of direct face-to-face contact during the COVID-19 (coronavirus disease 2019) pandemic would impair human empathy, an essential skill for maintaining relationships with others. Although physical activity amount relates to empathy, it remains unclear the effects of physical activity on empathy during the COVID-19 pandemic. Four hundred and twenty-six college students’ usual amounts of physical activity and sitting time were measured through monitoring from October to December 2020 with the questionnai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 8 publications
(12 reference statements)
0
4
0
Order By: Relevance
“…Previous studies have reported possibilities that physical activity and sports experiences alter self-reported empathy in healthy adults. 2-4 Since the current findings, human affective empathy could be sensitive to physical activity compared to cognitive empathy. However, the effect sizes of the current results were small; thus, we should investigate in depth.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Previous studies have reported possibilities that physical activity and sports experiences alter self-reported empathy in healthy adults. 2-4 Since the current findings, human affective empathy could be sensitive to physical activity compared to cognitive empathy. However, the effect sizes of the current results were small; thus, we should investigate in depth.…”
Section: Discussionmentioning
confidence: 60%
“…Although it is difficult to determine the causality, an increase in physical activity levels in college students would be a possibility to contribute to making their relationship better with family via increasing affective empathy, based on current results (Table 2) and previous studies. 4,10 Thus, our findings suggest that increasing physical activity levels after easing campus-access-restriction would lead to a better quality of life in young adults.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Oxytocin is also associated with empathy (Meyer-Lindenberg et al, 2011), and several studies have reported that oxytocin administration enhances empathy and related behaviors in humans (Auyeung et al, 2015;Geng et al, 2018). Considering that physical activities also contribute to enhancing empathy (Shima et al, 2022a(Shima et al, , 2022b(Shima et al, , 2021c(Shima et al, , 2021a(Shima et al, , 2021b, it is conceivable that exercise-induced oxytocin secretion plays a role in enhancing empathy. Therefore, AR-based multi-person exercise may have more beneficial effects on enhancing empathy than standard exercise, warranting further investigation.…”
Section: Discussionmentioning
confidence: 99%